PENGARUH BRAND IMAGE, KUALITAS PRODUK, PRESEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN MODERASI DIGITAL MARKETING: PENGARUH BRAND IMAGE, KUALITAS PRODUK, PRESEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN MODERASI DIGITAL MARKETING - Vendi Guardiola Guardiola; Henry Susanto Pranoto (LPPM Universitas Buddhi Dharma, 2024)
Noodles are a popular food in Indonesia with various advantages such as practical and fast preparation with digital marketing which is increasingly developing rapidly and its users, this makes the mie gaga product with the digital marketing carried out by mie gaga interesting to research. With various factors in consumer decisions in purchasing products. This research gathered 100 respondents who were Gaga noodle consumers aged 17-46 and domiciled in Surabaya. This research uses the Structural Equation Model (SEM) data analysis method using Smart Partial Least Square. The results of this research are that brand image on purchasing decisions has significant and positive results, product quality at purchasing decisions has a significant influence, price perception on purchasing decisions has an influence positively and significantly, digital marketing is unable to moderate brand image and product quality, and digital marketing moderates price perceptions on purchasing decisions by weakening, brand image has a positive and significant influence on purchasing decisions, product quality has a positive and significant influence on purchasing decisions, Price perception has a positive and significant effect on purchasing decisions, digital marketing is unable to moderate brand image and product quality on purchasing decisions, and digital marketing moderation weakens price perception on purchasing decisions.